Applying the Principle of Methodological Pluralism in the study of Socio-Economic Development - SMIRNOV, Vladimir; MERKUSHOVA, Natalia; KOMAROVA, Julia (Journal of Advanced Research in Law and Economics; Vol 6 No 2 (2015): JARLE Volume VI Issue 2(12) Summer 2015, 2016)
Changes in the nature and type of world social development are evaluated from different perspectives. The principle of methodological pluralism involves the use of different approaches. He is concretized in the form of an integrative approach. Socio-economic development is viewed as a multi-pronged interconnected process. One of the defining vectors of development is the direct subject-subject interaction between economic agents. This interaction is manifested in all the other basic characteristics of a developing economy and gives them a special quality. Another development is the vector orientation of production to create economic benefits to meet the needs of the highest order. Following vector of development is the increase in the economy and in society such specific services, such as information. Vector of development is a dialectical process of concentration and centralization of production and capital. Important vector of development is the specification of property rights on the basis of various quality changes. New forms, subjects, objects (including intangible assets) occur continuously. An important vector of the current world economic development is to strengthen innovation orientation. Vector of economic development is the increasing interdependence of economic actors, not only in the scale of the national economy, but also on a global scale. Developments in either direction causes quantitative and qualitative changes in other fields, in turn, receives a similar action. Multivectorness development increases. Vectors of development are interrelated, are in the system must be consistent with use.
Keywords: socio-economic development, vector, integrative approach